Prenatal Management of Compromised Fetus - Begum, Shamsun Nahar; Kabir, Nazneen; Akhter, Fahima (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Compromised fetuses are those who are at increased risk in intrauterine life due to various factor resulting in increased mortality & morbidity. Fetal compromise in pregnancy is difficult to assess. Diagnostic skills for fetal diseases have improved enormously, but therapeutic approaches remains limited. The Fetus should be considered as a separate individual and fetal medicine now needs to move into phase of evidence based management. Due to relative rarity of fetal disorder, a multicentre study is needed and this is the challenge for the next decade of fetal medicine. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(2) : 92-99